Application of the Problem Based Learning Model to Improve the Learning Outcomes of Students of PAI Subjects in Integrated Islamic Elementary Schools - Nur Afifah; Siti Noor Lina (FITK UIN Walisongo Semarang, 2025)
This study aims to describe the implementation and improvement of learning outcomes of students in class IA IT SD IT Ribhul Ulum Kedungmutih in the subject of Islamic Religious Education (PAI) material Faith in Allah SWT through the application of the Problem-Based Learning (PBL) learning model. The type of research used is Classroom Action Research (PTK) which is conducted in two cycles. The research subjects consisted of 18 students of class IA. Data collection was carried out through written tests and observation sheets. The results showed that in the first cycle, there were 8 out of 18 students (44%) who achieved the Minimum Completeness Criteria (KKM) of 70 with an average grade of 64. In cycle II, there was a significant increase, where all students (100%) achieved KKM with an average class score increasing to 80. This shows that the application of the PBL model contributes positively to improving students' understanding, especially in the material of Faith in Allah SWT. The implementation of learning with PBL provides a more active and meaningful learning experience so as to encourage a significant improvement in student learning outcomes. Thus, the PBL model can be an effective learning strategy recommended in the context of Islamic religious education at the elementary school level.